Synthesis and Antimicrobial Activity of 3-Cyano-4-imino-9-methoxy-4H-pyrimido [2, 1-b] pyrimido [4, 5-b] quinoline and 2-Substituted Derivatives - S. P. Vartale; N. K. Halikar; Y. D. Pawar (Journal of Chemistry)
The 2-amino-7-methoxypyrimido[4,5-b]quinoline (1) on treatment with bis(methylthio)methylene malononitrile (2) in ethyl alcohol and catalytic amount of TEA gives 3-cyano-4-imino-9-methoxy-2-methythio-4H-pyrimido[2,1-b]pyrimido[4,5-b]quinoline (3). The latter were further reacted with selected N-, O-, and C-nucleophiles such as aryl amines, hetryl amines, substituted phenols, and compounds containing an active methylene group.